PENGARUH PENGGUNAAN LARUTAN ALKALI DALAM UJI FOURIER TRANSFORM INFRARED PADA KOMPOSIT TERMOPLASTIK BERPENGISI SERBUK SERABUT KELAPA - Johannes Leonard S, Harry Abrido S, Maulida (Jurnal Teknik Kimia USU, 2013)
Composite is a combination of two different materials to obtain a material with physical and mechanical properties are better than any of its constituent parts. One of the composite types which is much produced is composite with powdered natural fiber filler. This research uses the used polypropylene matrix and powdered coconut fiber as filler treated with Sodium Hydroxide (NaOH). The ratio of the matrix and the filler is 85:15. This ratio is the optimum value obtained by the composite tensile strength with ratio 100:0, 95:5, 90:10 and 85:15. The purpose of this study was to determine the effect of the use of an alkaline solution of the resulting composite properties especially towards lignin level, with Fourier Transform Infrared (FTIR) test on composite material used polypropylene with powdered coconut fiber as filler. The method used in the manufacture of composites is the method of extrusion. The matrix form of the used polypropylene mixed with coconut fiber powder that has been soaked with NaOH, then mixed in a container, then put into the extruder operating temperature 1750C, printed using a hot press at a temperature of 1750C, and cut into pieces appropriate testing. The results showed that the optimum processing occurs with NaOH for 2 days. The FTIR test result, showed that –OH cluster switch occured, be seen from the shifting of absortion band from 3417.04 cm-1 to 3476.84 cm-1 for the powdered coconut fiber and the shifting of absortion band from 3343.75 cm-1 to 3192.33 cm-1 for the composite, which is the –OH cluster of the lignin. Keywords : composite, used polypropylene, coconut fiber, NaOH, FTIR test, lignin level